2021
DOI: 10.2147/ijn.s304526
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolin-Targeting AS1411 Aptamer-Modified Micelle for the Co-Delivery of Doxorubicin and miR-519c to Improve the Therapeutic Efficacy in Hepatocellular Carcinoma Treatment

Abstract: Background: Multidrug resistance (MDR) has emerged to be a major hindrance in cancer therapy, which contributes to the reduced sensitivity of cancer cells toward chemotherapeutic drugs mainly owing to the over-expression of drug efflux transporters. The combination of gene therapy and chemotherapy has been considered as a potential approach to improve the anti-cancer efficacy by reversing the MDR effect. Materials and Methods: The AS1411 aptamer-functionalized micelles were constructed through an emulsion/solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…It has been documented that HepG2 cells overexpress nucleolin and AS1411 aptamers can actively recognize and bind with nucleolin . Inspired by this, AS1411-mediated targeted accumulation of the SFTON in HepG2 tumor is expected.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…It has been documented that HepG2 cells overexpress nucleolin and AS1411 aptamers can actively recognize and bind with nucleolin . Inspired by this, AS1411-mediated targeted accumulation of the SFTON in HepG2 tumor is expected.…”
Section: Resultsmentioning
confidence: 97%
“…It has been documented that HepG2 cells overexpress nucleolin 38 and AS1411 aptamers can actively recognize and bind with nucleolin. 39 Inspired by this, AS1411mediated targeted accumulation of the SFTON in HepG2 tumor is expected. Quantitative data derived from inductively coupled plasma atomic emission spectrometry (ICP-AES) also demonstrate it via monitoring the Zn content, where the accumulation of AS1411-chelated PMCS in HepG2 tumors is twofold higher than that of PMCS alone 6 h after injection of the corresponding samples (Figure 6a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Liu et al [ 22 ] reported that the encapsulation of meta -tetra(hydroxyphenyl)chlorine, a photosensitizer, in P23 micelles effectively increased blood circulation kinetics and ultimately enhanced selective photocytotoxicity on A431 cells. As with other studies reporting that multidrug resistance is effectively reversed by combining gene therapy and chemotherapy, Liang et al [ 23 ] reported that the construction of AS1411 aptamer-functionalized micelles by encapsulating doxorubicin and miR-519c enhanced active targeting and suppressedthe multidrug resistance in the hepatocellular carcinoma cell line (HepG2).Apart from cancer, micelles can also be used in the treatment of other diseases such as cardiac toxicity, rheumatoid arthritis, etc. After myocardial infarction, the recruitment of monocytes to the infract through the CCR2 chemokine receptorprolongs inflammation and worsens clinical outcomes.…”
Section: Types Of Nanoparticlesmentioning
confidence: 89%
“…For example, encapsulation of fluorescent 1-pyrenecarboxaldehyde (Py-CHO) molecules into block copolymer-based micelles not only provides a hydrophobic environment for the accommodation of Py-CHO, but also enhances its fluorescence properties ( Gao et al, 2018 ). The excellent stability of micelles and the ideal encapsulation and protection of hydrophobic probes ( Cheng et al, 2021 ; Liang et al, 2021 ) have received much attention in the field of biochemical analysis.…”
Section: Introductionmentioning
confidence: 99%